AKP’nin Suriyeli Göçmen Söylemini Türkiye’nin Jeopolitik Senaryosuyla Birlikte Okumak - Balkılıç, Özgür; Lloyd, Fatma Armağan Teke (My University, 2020)
Although AKP employed an open door policy in dealing with Syrian refugee crisis, the way that it shaped its discursive lexicon is puzzling. AKP’s discourse does not easily overlap with familiar theories and practices of international migration. Rather for AKP, this crisis was an indication of a broad range problems in the international system, extending from the categorization of migrants to the problems of morality and leadership. As such, Turkey’s geopolitical script might provide analytical insights to comprehend AK’s seemingly confusing and extended discourse. Specifically, this article focused on two themes in this discourse. First, AKP has utilized a religious based definition of “guest” to refer to Syrian migrants rather than any statuses specified in official regulations. Second, AKP reads the Syrian refugee crisis as a repercussion of larger political and moral crises of the international system, in which it demarcates a leadership role for Turkey.

AKP Suriyeli mülteci krizi ile baş etmek için uzun bir süre boyunca açık kapı politikası uygulamasına karşın, 2011-2018 yılları arasında konu üzerine geliştirdiği söylemsel pratiği kafa karıştırıcıydı.Zira,busöylemselpratikuluslararasıgöçkuramlarıvepratikleriörüntüsünü tamolaraktakipetmiyordu. Aslında AKP için göçmen krizi,Batı’nın ahlaki ve lider lik sorunlarının geniş yansımasının bir ürünüydü. Suriye göçmen krizini uluslararası sistemin bir çöküşünün sonucu olarak okuyan Türkiye’nin dışpolitika pratiklerini temellendirdiğivemeşrulaştırdığıjeopolitiksenaryosuAKP’nin görünürde kafa karıştırıcı söylemini kavramamız için bize analitik bir çerçeve sunabilir. Bu makale söz konusu söylemde iki temaya odaklanmaktadır. Birincisi, AKP Suriyeli göçmenleri tanımlarken resmi düzenlemelerde belirtilen herhangi bir statüden ziyade dini temelli bir “misafir” kavramına başvurmaktadır. İkincisi, AKP Suriyeli mülteci krizini, içerisinde Türkiye’ye bir liderlik rolü payesi biçecek şekilde, uluslararasısistemin daha geniş siyasi ve ahlaki bir krizinin bir sonucu olarak ele almaktadır.
Reading the Akp’s Discourse on Syrian Migrants from the Lens of Turkey’s Geopolitical Script
Keywords: Uluslararası İlişkiler; Siyasi Bilimler; Sağlık Politikaları Ve Hizmetleri